Методи оцінки венчурних проектів: особливості та можливі підходи - Геращенко, О. П. (Ways to Improve Construction Efficiency, 2012)
The problems of venture investment in innovation activities and their solutions. Characteristic features, drawbacks and benefits of new business for our kind of investment. The analysis of market venture capital investment in Ukraine. Revealed negative factors that hinder the development of venture capital industry in Ukraine, and the measures on the revival of venture investing.